In Silico Comparison of Disulfide-Bearing and Disulfide-Free Phytases among Microorganisms - Ebrahimi, Shirin; Jamei, Rashid; Ghasemian, Abdolmajid; Mostafavi, Seyyed Khalil Shokouhi (Journal of Pharmacy and Nutrition Sciences, 2017)
Phytases are degrading enzymes that hydrolyze phytate (myo inositol hexa kis phosphate) to release a series of lower phosphate esters of myoinositol and orthophosphate. Phytase successfully used as an animal feed additive to increase the bioavailability of phosphate from phytic acid in the grain-based diets of poultry and swine. In order to investigate structural relationships between disulfide-bearing phytases and disulfide-free phytases, 9 phytases with resolved three-dimensional (3D) structure were retrieved as pdb and FASFA format from Protein Data Bank server and were analyzed using various tools and software. The results showed that 6 out of 9 phytases carry three or more disulfid bonds while the others lack any disulfide bonds. Our results also demonstrated that there is a remarkable correlation between the presence of disulfide bond and the number of amino acid in each phytase which means the larger enzymes contain three or more disulfide bonds whereas the enzymes containing less than 400 amino acids lack any disulfide bond. Additionally, in order to dig out the structure of phytases, some chemical and physical characteristics of phytases such as aliphatic index (AI), isoelectric pH (PI), amino acids percentage, molecular weights (MW) and 3D structure of phytases were analyzed. Results showed that phytases containing disulfide bonds have some identical characteristic including glycine percentage, AI, and 3D structure rather than disulfide-free phytases do. Moreover, evolutionary surveys by means of alignment studies and evaluations were conducted. Evolutionary analysis represented that phytases with disulfide bond most probably exhibited the same evolutionary course.